ANALYSIS OF DIGITAL MARKETING IMPLEMENTATION AS A STRATEGY IN INCREASING MSME PRODUCT SALES: (Case Study of MSME Syifa Bakery) - Rahardjo, Kusuma Adi (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
In the current business landscape, the role of digital marketing in driving sales and shaping marketing strategies has become increasingly essential, especially for Micro, Small, and Medium-sized Enterprises (MSMEs). This study aims to determine the effects of digital marketing on sales, marketing strategies, and the challenges associated with implementing digital marketing for MSMEs, using Syifa Bakery as a case study. The research adopts an observational descriptive approach, utilizing structured and in-depth interviews for data collection. The study's findings reveal that the digital marketing initiatives undertaken by Syifa Bakery, an MSME, significantly contribute to increased sales. Digital marketing proves to be cost-effective, convenient, and accessible at all times. The primary strategy employed for product marketing through digital channels includes the use of social media platforms like Facebook, Instagram, WhatsApp status updates, and live streaming on Facebook. However, the implementation encounters challenges such as unreliable internet connections, delivery delays, insufficient marketing and design personnel, and instances of transaction fraud and manipulation of administrative contact information. Thus, the study demonstrates the multifaceted nature of digital marketing implementation.